Attitudes to the Polish language of Polish youth minority living in Eišiškės - Geben, Kinga; Borisewska, Aneta (Vilnius University Open Series, 2021)
The aim of the article is to analyze language attitudes expressed by young people belonging to the Polish ethnic minority living in Eišiškės. The material for this research was collected in 2020 by student Aneta Borisevska on the basis of a survey developed in the project “Sociolinguistic map of Lithuania: city and town (2013)”. The results of the survey show that the Polish language is assessed ambiguously by the respondents: the common Polish language is considered prestigious and necessary for contacts in Poland, but the Polish dialect is considered mixed and unsuitable for use in Vilnius or Poland. Young respondents state that they will need the Lithuanian language the most to study and work in Lithuania. In Eišiškės, there is a tendency to use the Lithuanian language more widely, the Polish dialect it is mostly spoken at home and with acquaintances.
Keywords: language attitudes; diglossia; Eišiškės; youth